Beyond flash sintering: How the flash event could change ceramics and glass processing. (October 2020) - Biesuz, Mattia; Sglavo, Vincenzo M.
Abstract: The broad and far-reaching (beyond sintering) implications of flash processes are critically assessed. Different mass transport-based flash-like technologies are currently emerging: synthesis, pyrolysis, joining, plastic and viscous shaping. These could be used to develop new high entropy materials, to change wetting properties in ceramic-metals joints, to shape ceramics by plastic deformation. Moreover, the flash can change the chemistry of oxides thus introducing far-from-equilibrium crystallographic and/or electronic features. The development of predictive models to determine the field-current-material interactions and the produced defects could represent a new tool to design and engineer ceramics in the next future.